2016
DOI: 10.3389/fpls.2016.01531
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Costs of Reproduction in Mango – Vegetative Growth Matters

Abstract: Irregular fruit production across successive years is a major issue that limits the profitability of most temperate and tropical fruit crops. It is particularly affected by the reciprocal relationships between vegetative and reproductive growth. The concept of the costs of reproduction is defined in terms of losses in the potential future reproductive success caused by current investment in reproduction. This concept, developed in ecology and evolutionary biology, could provide a methodological framework to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 82 publications
3
12
0
Order By: Relevance
“…Moreover, the structural (Lauri and Trottier 2004, Normand et al 2009, Gaaliche et al 2011) and/or temporal (Wilkie et al 2008, Dambreville et al 2013) characteristics of vegetative growth may affect flowering. These findings on mango as well as on some other species (Hasegawa and Takeda 2001, in forest trees; Lauri and Trottier 2004, in apple) strongly support the idea that vegetative growth Previous results on mango highlight three negative effects of reproduction on the outgrowth of lateral vegetative buds, leading to less vegetative growth: (1) Inflorescence and fruit inhibit lateral bud outgrowth as long as they are present on the bearing axis (Singh and Singh 1969); (2) Flowering and fruiting decrease the probability of vegetative bud outgrowth at the axis scale compared to quiescent axes (Capelli et al 2016); and (3) Fruiting delays vegetative bud outgrowth when it occurs (Dambreville et al 2013). Two hypotheses, possibly complementary, are generally put forward to explain the negative effects of high fruit load on vegetative growth: (1) hormone synthesis by the reproductive organs that inhibit vegetative growth; and (2) carbohydrate mobilization by fruit, which reduces their availability for vegetative growth (Smith andSamach 2013, Martinez-Alcántara et al 2015).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, the structural (Lauri and Trottier 2004, Normand et al 2009, Gaaliche et al 2011) and/or temporal (Wilkie et al 2008, Dambreville et al 2013) characteristics of vegetative growth may affect flowering. These findings on mango as well as on some other species (Hasegawa and Takeda 2001, in forest trees; Lauri and Trottier 2004, in apple) strongly support the idea that vegetative growth Previous results on mango highlight three negative effects of reproduction on the outgrowth of lateral vegetative buds, leading to less vegetative growth: (1) Inflorescence and fruit inhibit lateral bud outgrowth as long as they are present on the bearing axis (Singh and Singh 1969); (2) Flowering and fruiting decrease the probability of vegetative bud outgrowth at the axis scale compared to quiescent axes (Capelli et al 2016); and (3) Fruiting delays vegetative bud outgrowth when it occurs (Dambreville et al 2013). Two hypotheses, possibly complementary, are generally put forward to explain the negative effects of high fruit load on vegetative growth: (1) hormone synthesis by the reproductive organs that inhibit vegetative growth; and (2) carbohydrate mobilization by fruit, which reduces their availability for vegetative growth (Smith andSamach 2013, Martinez-Alcántara et al 2015).…”
mentioning
confidence: 64%
“…Reproduction has negative effects on vegetative growth in various temperate and tropical fruit tree species (Lauri and Térouanne 1999, in apple;Costes et al 2000, in apricot;Berman and DeJong 2003 in peach;Lovatt 2010 in avocado;Capelli et al 2016, in mango), with a cultivar-dependent effect (Capelli et al 2016). On the other hand, flower and fruit production is positively related to the quantity of previous vegetative growth (Lovatt 2010.…”
mentioning
confidence: 99%
“…In order to thrive under resource competition, plants tend to gain larger size through rapid vegetative growth (Zust et al, 2015). Previous studies have also shown that plants do not usually initiate costly flower organ development (Williams, 1966;Capelli et al, 2016) until they reach a certain threshold in size (Samson and Werk, 1986;Weiner et al, 1988), and the magnitude and form of reproduction are limited by the level of previous resource reserves (Capelli et al, 2016). In T2, the active end of vegetative growth of the shoot and the slow development of the LR show that the plant allocated resources well, as these two processes apparently avoided competing with the subsequently initiated sexual reproductive growth for resources.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of lateral daughter GUs depended on the fate and position of the ancestor GU. The flowering and fruiting ancestor GUs produced more lateral daughter GUs (3.4 and 4.2, respectively) than quiescent ancestor GUs (2.4), probably due to the loss of apical dominance with apical flowering ( Normand et al , 2009 ; Capelli et al ., 2016 ).…”
Section: Model Descriptionmentioning
confidence: 99%